2010
DOI: 10.1093/jac/dkq481
|View full text |Cite
|
Sign up to set email alerts
|

IncA/C plasmids mediate antimicrobial resistance linked to virulence genes in the Spanish clone of the emerging Salmonella enterica serotype 4,[5],12:i:−

Abstract: IncA/C plasmids are responsible for multidrug resistance in an increasing number of relevant human and animal bacterial pathogens, and hence are regarded as an important threat to public health. Those found in the Spanish clone of Salmonella 4,5,12:i:- constitute a relevant example of short-term evolution, and could have been involved in the successful adaptation of this pathogen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
54
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 33 publications
3
54
0
Order By: Relevance
“…The isolates were given designation consisting of LSP (for Laboratorio de Salud Pública) followed by a code number/year of isolation. Nineteen isolates had been previously investigated with regard to phage type, PFGE profile, plasmid content, and antimicrobial susceptibility and responsible genes (11). Two additional isolates (LSP 127/00 and LSP 148/ 00) were similarly characterized for the present study.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The isolates were given designation consisting of LSP (for Laboratorio de Salud Pública) followed by a code number/year of isolation. Nineteen isolates had been previously investigated with regard to phage type, PFGE profile, plasmid content, and antimicrobial susceptibility and responsible genes (11). Two additional isolates (LSP 127/00 and LSP 148/ 00) were similarly characterized for the present study.…”
Section: Methodsmentioning
confidence: 99%
“…Mainly due to its connection with an increasing number of human cases of salmonellosis, a number of studies have focused on its emergence and evolution (1,2). It was shown that S. 4, [5],12:i:Ϫ is closely related to S. Typhimurium (3)(4)(5)(6)(7)(8)(9)(10)(11). The monophasic serovar does not express the second-phase flagellar antigen, and different mutations and/or deletions affecting the fljAB operon (encoding a negative regulator of the fliC gene for the first-phase flagellar antigen and the second-phase antigen, respectively) and surrounding genes have been detected (6,9,10,12,13).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…A more likely scenario based upon recent work is that an ancestral plasmid type possessed an IncFIIA/IncFIB backbone containing spv, prf, and pef and separated following the divergence of serogroups and that the plasmid lineages subsequently underwent recombination events, resulting in the current virulence plasmid profiles. Interestingly, there is little evidence of extensive transfer of virulence plasmids among the Salmonella serovars, even though their transfer in vivo has been documented (129). The horizontal transfer of these plasmids is likely a neutral trait in Salmonella, and thus, transfer between serovars is not strongly selected (130,131).…”
Section: Role Of Plasmids In Salmonella Genome Evolutionmentioning
confidence: 99%